Medial plantar artery perforator (MPAP) flap is an ideal option for reconstruction of complex soft tissue defect in the finger: Clinical experience from 11 cases - Xiang Xu; Cheng Wang; Zhenbing Chen; Jin Li (Frontiers in Surgery, 2022)
IntroductionSoft tissue defects of fingers are common in reconstructive plastic surgery, and reconstruction of the defects remains challenging for plastic surgeons. In our study, we reported our experience in finger reconstruction with a medial plantar artery perforator (MPAP) flap, especially using a lobulated MPAP flap for the complex multifinger soft defect.Patients and methodsFrom the period April 2012 to October 2018, 11 patients (9 males and 2 females) with an average age of 44 years old (ranging from 11 to 58) received finger reconstruction with a free MPAP flap. In total, 11 flaps (8 single-lobulated flaps and 3 two-lobulated flaps) were raised from the ipsilateral or contralateral instep area. Trauma and scar contracture caused hand soft tissue loss in all cases.ResultsThe sizes of the flaps ranged from 2×3 to 5×7.5 cm2. All flaps survived intact with no complications. One donor site was closed primarily, and other donor sites were covered with a full-thickness skin graft. The mean follow-up time was 6 months (ranging from 3 to 8 months). During the follow-up period, the patients were satisfied with their appearance without any traces of flap plastic surgery.ConclusionThe MPAP flap is a reliable and acceptable option for the reconstruction of complex soft tissue defects in the finger. Depending on the two branches of the medial plantar artery, the use of the lobulated MPAP flap holds promise in the treatment of multifinger soft tissue defects.